Integrasi Mesin Penukar Botol Plastik dalam Event Kota Solo sebagai Upaya Meningkatkan Daya Saing Berbasis Budaya, Pariwisata, dan Ekonomi Kreatif - Linda Dwi Puspita Sari; Intan Riyani Fatimah; Nadiya Nur Rahma Fatikha (Badan Riset dan Inovasi Daerah Kota Surakarta, 2025)
This research aims to reduce waste particularly plastic waste in the city of Surakarta (Solo) by integrating Reverse Vending Machines (RVM) into city events as an effort to enhance competitiveness in the fields of culture, tourism, and the creative economy. Surakarta (Solo) is well known as a cultural center with significant potential in tourism and creative industries. However, various cultural and sporting events often generate large amounts of plastic waste, especially from single-use plastic bottles. To address this issue, the implementation of Reverse Vending Machines (RVM) at city events can serve as an innovative solution that supports competitiveness based on culture, tourism, and the creative economy. RVMs provide the community with an opportunity to exchange used plastic bottles for points or digital incentives, encouraging active participation in waste management, fostering a sustainable economic ecosystem, and increasing environmental awareness among residents. The application of this technology aligns with Asta Cita Surakarta, which outlines the eight regional priority programs of the City of Surakarta for 2025–2030, as well as the Sustainable Development Goals (SDGs). The writing method of this research employs a quantitative descriptive approach, chosen to analyze existing data (secondary data) in order to evaluate the relationship between the potential implementation of RVMs and the competitiveness of Solo City in culture, tourism, and the creative economy. Therefore, integrating RVMs into city events not only helps reduce plastic waste but also serves as an effective strategy to strengthen Solo’s competitiveness through the synergy of cultural preservation, tourism development, and creative economic growth.